DAMPAK PEWARTAAN MELALUI MEDIA DIGITAL - Vinsensius Bawa Toron (STP Reinha Larantuka, 2021)
This article is entitled The Impact of Publication Through Digital Media. The approach method used by the author is a survey of the communication of young people, parents and religious leaders who follow the proclamation through official and unofficial digital media sites. The survey used a sample of 50 official and unofficial media and the survey results show that young people, parents and religious leaders are interested in using digital media because reporting is more effective, creative and not boring by applying various reporting methods. But on the other hand, young people and parents experience confusion, because through unofficial media sites, journalists build their personal opinions, blurring the content of reporting and preaching is more directed to personal business, not at the core of the teachings of the Christian faith, namely the interests of salvation. Artikel ini berjudul Dampak Pewartaan Melalui Media Digital. Metode pendekatan yang digunakan penulis adalah survey terhadap komunikasi para orang muda, orangtua dan tokoh agama yang mengikuti pewartaan melalui situs media digital resmi maupun tidak resmi. Survey dengan sample yang digunakan sebanyak 50 media resmi dan tidak resmi dan hasil survey menunjukkan bahwa orang muda, orangtua dan tokoh agama tertarik menggunakan media digital karena pewartaan lebih efektif, kreatif dan tidak membosankan dengan menerapkan metode pewartaan yang variatif. Namun di sisi lain, orang muda dan orangtua mengalami kebingungan, karena melalui situs media tidak resmi, pewarta membangun opini pribadinya mengaburkan isi pewartaan dan pewartaan diwartakan lebih mengarah kepada bisnis pribadi bukan pada inti dari ajaran iman kristiani yakni kepentingan keselamatan.